Current trends and challenges on migration from a human rights perspective - González Morales, Felipe (2025)
The scope and complexity of migration in recent years have led to a scenario in which a series of new trends have emerged, some of them problematic from the point of view of their consistency with international human rights standards. This makes it necessary to address the current challenges to ensure such consistency. The article analyzes the main current trends and challenges and makes a series of proposals to strengthen the human rights of migrants.